Evidence for the interplanetary electric potential? WIND observations of electrostatic fluctuations - C. Lacombe (Annales Geophysicae, 2002)
In the solar wind at 1 AU, coherent electrostatic waveforms in the ion acoustic frequency range (~ 1 kHz) have been observed by the Time Domain Sampler (TDS) instrument on the Wind spacecraft. Small drops of electrostatic potential (Df > 10-3 V) have been found across some of these waveforms, which can thus be considered as weak double layers (Mangeney et al., 1999). The rate of occurrence of these potential drops, at 1 AU, is estimated by a comparison of the TDS data with simultaneous data of another Wind instrument, the Thermal Noise Receiver (TNR), which measures continuously the thermal and non-thermal electric spectra above 4 kHz. We assume that the potential drops have a constant amplitude and a constant rate of occurrence between the Sun and the Earth. The total potential drop between the Sun and the Earth, which results from a succession of small potential drops during the Sun-Earth travel time, is then found to be about 300 V to 1000 V, of the same order of magnitude as the interplanetary potential implied by a two-fluid or an exospheric model of the solar wind: the interplanetary potential may manifest itself as a succession of weak double layers. We also find that the hourly average of the energy of the non-thermal ion acoustic waves, observed on TNR between 4 and 6 kHz, is correlated to the interplanetary electrostatic field, parallel to the spiral magnetic field, calculated with a two-fluid model: this is another evidence of a relation between the interplanetary electrostatic field and the electrostatic fluctuations in the ion acoustic range. We have yet to discuss the role of the Doppler effect, which is strong for ion acoustic waves in the solar wind, and which can bias the measure of the ion acoustic wave energy in the narrow band 4–6 kHz. Key words. Interplanetary physics (plasma waves and turbulence; solar wind plasma) Space plasma physics (electro-static structures)